Comparing of the behaviour of iterative methods based on different means - Amat, Sergio; Busquier, Sonia; Hernández-Verón, M A; Magreñán, Á. Alberto; Orcos, Lara (AIP Conference Proceedings, 2021)
Based on the modification of family of iterative processes of Chebyshev-Halley presented by M. Kansal et al. in [2], whose convergence is cubic, we will present in this talk a comparison between the behaviour of some members of the family in which some different means are used. We will also study the influence of that mean in the convergence of the methods
Keywords: semilocal convergence; system of nonlinear equations; multiple roots; Scopus(2); WOS(2)